2010
DOI: 10.1111/j.1600-0846.2010.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivomeasurement of the human epidermal thickness in different localizations by multiphoton laser tomography

Abstract: The method presented here provides a novel in vivo investigation tool for the measurement of epidermal morphometric parameters that may be useful for the observation of epidermal changes over time in skin disorders, therapy side effects or in cosmetic science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 22 publications
5
71
0
2
Order By: Relevance
“…Since the epidermal thickness typically ranges from 60 to 300 μm, 10,11 our model assumes that all wavelengths in our range of interest penetrate through the epidermis and hence, the diffuse reflectance detected from the skin contains contributions from both epidermal and dermal layers, shown schematically in Fig. 2.…”
Section: Modelmentioning
confidence: 99%
“…Since the epidermal thickness typically ranges from 60 to 300 μm, 10,11 our model assumes that all wavelengths in our range of interest penetrate through the epidermis and hence, the diffuse reflectance detected from the skin contains contributions from both epidermal and dermal layers, shown schematically in Fig. 2.…”
Section: Modelmentioning
confidence: 99%
“…In order to determine the characteristic features associated with different skin pathologies, MPT and OCT images obtained from these pathological lesions were compared with the healthy skin. However, it has been shown that typical morphological features of normal skin visible in MPT and OCT vary from site to site in the body depending on age, gender and skin type [41,42]. Similarly, quantitative parameters extracted from MPT and OCT images of normal skin such as cell and nucleus diameter, epi- dermal thickness, nucleus to cytoplasm ratio, cell density and SHG to autofluorescence ageing index of dermis exhibit intra-personal and inter-personal differences [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…BCC originates from the basal layer of the epidermis, the top most layer of the human skin. Typically, the human epidermis has an average thickness of around 100 µm [19,20]. In our numerical scanning example, the human skin consists of a 300 µm thick healthy skin and a patch of BCC, also with thickness 300 µm encapsulated within the healthy skin.…”
Section: Bcc Detection Based On Reflected Terahertz Pulsementioning
confidence: 99%